253 Anti-TIGIT antibodies require enhanced FcγR co-engagement for optimal T and NK cell-dependent anti-tumor immunity. (10th December 2020) - Ward, Rebecca; Paltrinieri, Elena; Marques, Marilyn; Iyer, Priyadarshini; Dietrich, Sylvia; Waight, Jeremy; Bushell, Mark; Wilson, Nicholas; Buell, Jennifer; Savitsky, David; Chand, Dhan
Abstract : Background: T-cell immunoreceptor with Ig and ITIM domains (TIGIT) is an important negative regulator of the immune response to cancer that contributes to resistance/relapse to anti-PD-1 therapy. 1 In clinical trials, anti-human (h) TIGIT antibodies have shown promising activity in combination with anti-PD-1/PD-L1 antibodies for the treatment of various solid tumors. 2 However, the optimal format for anti-TIGIT antibodies remains controversial. Here we describe a novel Fcγ receptor (FcγR)-dependent mechanism of action that is critical for enhancing T and NK cell anti-tumor immunity, and, further informs on the optimal design of anti-TIGIT antibodies. Methods: We investigated a panel of Fc-silent, Fc-competent, and Fc-engineered anti-mouse (m) TIGIT antibody variants in syngeneic murine CT26 tumor-bearing or B16F10 pseudo-metastases models. To further elucidate the relative contribution of T and NK cells in controlling tumor growth, we assessed the activity of Fc-engineered anti-TIGIT antibodies in NK cell-depleted or T cell-deficient (Nu-Foxn1nu) CT26 tumor-bearing mice. Immune-related pharmacodynamic changes in the tumor microenvironment were assessed by flow cytometry. We further validated these findings in primary human T and NK cell activation assays using Fc-engineered anti-human TIGIT antibodies. Results: The Fc-engineered anti-mTIGIT antibody, which demonstrates enhanced binding to mouse FcγRIV, was the only variant to deliver single agent anti-tumor activity. The Fc-enhanced variant outperformed the Fc-competent variant while the Fc-inert variant had no anti-tumor activity. Tumor control by anti-mTIGIT antibodies was not dependent on Treg depletion, but rather on increased frequency of CD8+ T cells and activated NK cells (Ki67, IFNγ, CD107a and TRAIL) in the tumor microenvironment. Concordant with observations in the mouse, Fc-engineered anti-hTIGIT antibodies with improved binding to FcγRIIIA demonstrate superior T and NK cell activation in PBMC-based assays compared to a standard hIgG1 variant. Notably, superior activity of the Fc-engineered anti-hTIGIT antibody was observed from PBMC donors that express either high or low affinity FcγRIIIA. Blockade of FcγRIIIA or depletion of CD14+ and CD56+ cells reduced the functional activity of the Fc-enhanced anti-TIGIT antibody, confirming the requirement for FcγR co-engagement to maximize T cell responses. Conclusions: Our data demonstrate the importance of FcγR co-engagement by anti-TIGIT antibodies to promote immune activation and tumor control. First generation anti-TIGIT antibodies are not optimally designed to co-engage all FcγRIIIA variants. However, Fc-enhanced anti-TIGIT antibodies unlock a novel FcγR-dependent mechanism of action to enhance T and NK cell-dependent anti-tumor immunity and further improve therapeutic outcomes. References: Johnston RJ, et al., The immunoreceptor TIGIT regulates antitumor and antiviral CD8(+) T cell effector function. Cancer Cell 2014; 26 :923–37. Rodriguez-Abreu D, et al., Primary analysis of a randomized, double-blind, phase II study of the anti-TIGIT antibody tiragolumab (tira) plus atezolizumab (atezo) versus placebo plus atezo as first-line (1L) treatment in patients with PD-L1-selected NSCLC (CITYSCAPE). Journal of Clinical Oncology 2020; 38 :15_suppl, 9503–9503.